Feline immunodeficiency virus infection: A comparative study of different diagnostic techniques - Mórtola, Eduardo Carlos (2004)
This study evaluated an indirect immunofluorescence assay (IFA) to detect feline immunodeficiency virus infection (FIV) antibody in a comprehensive epidemiological survey of FIV in Argentina. IFA modified in our laboratory, was compared with two other immunoassays, western blot (WB) and a sandwich immunochromatographic commercial kit (SI), and also with a direct polymerase chain reaction (PCR) method that detects proviral DNA. IFA showed to be a test with high sensitivity and specificity, and could be useful as a diagnostic tool in epidemiological studies. The presence of a low percentage of results with non-specific reactivity in the IFA could be resolved with further testing or use of an alternative method.